Gingival biotypes and its relation to biologic width, alveolar bone thickness, dehiscence and fenestration in mandibular anterior region: A CBCT analysis study - Abdulrahman Shaya Albughaylil; Arshad Jamal Sayed; Mona Abdulmohsen Alsoli; Mohammed Mutni Almutairi; Syed Fareed Mohsin; Safia Shoeb Shaikh; Khalid Ali Alsaykhan; Ibrahim Abdulaziz Albulayhid (Wolters Kluwer Medknow Publications, 2023)
Background: Gingival biotype and its relationship to biologic width and alveolar bone thickness may affect surgical periodontal therapy outcomes. Hence, it is vital to assess the gingival biotype prior to any of these treatments for its success. Aim: The study aims to compare the thick and thin gingival biotype in the mandibular anterior region concerning biologic width, buccal bone thickness, prevalence and distribution of dehiscence, and fenestration in lower anterior teeth. Materials and Methods: A total of 30 patients were selected for the study based on the inclusion and exclusion criteria. The Cone Beam Computed Tomography analysis was performed in the mandibular anterior area to assess gingival thickness (biotype), biologic width, buccal bone thickness, dehiscence, and fenestrations. The data were analyzed using SPSS version 26. An independent t-test was used to assess the relationship between the variables. Results: Our study identified an increased biologic width in the thick gingival biotype, a higher frequency of dehiscence in the thin gingival biotype than in the thick biotype, and a greater mean alveolar bone thickness in the thick biotype group. Conclusion: A statistical difference was not observed between the groups; however, the thick biotype showed better results than the thinner biotype for the periodontal parameters examined.